The Design of a Library Assistant Repository System - Hasibuan, Nuriah; Syafi'i, Muhammad Zakki; Fatwanto, Agung (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
An a Libraries aim to provide services to users, currently libraries must build a system design so that services to users continue to increase according to the times and technology, especially in reference services. Reference service is one that plays an important role in library services, this is where the information retrieval system includes providing assistance to users to find information and providing guidance to find and use reference collections. The Library is a library where most of its visitors are generations who are proficient in technology, so service innovation is needed that is able to provide something to meet their needs and culture. The purpose of this research is to provide an innovative design that can be applied when providing services to users. This research includes literature study research. The result of this research is the design of a reference service system that can be implemented in the library. This repository reference system can be used independently by visitors to the library in the process of searching for information, thereby simplifying and speeding up the information search process, also this innovation will simplify the librarian's task of carrying out reference services and streamline time and energy.